A reverse index futures split effect on liquidity and market dynamics. (2017) - Athanasios, Fassas; Nikolas, Hourvouliades
This paper examines the relationship between daily price variability and trading activity dynamics six months before and after the redesign of FTSE/ATHEX large cap futures contract in June 2016. Although contract and tick size is a critical factor for the viability of a futures market, there has been limited empirical research on this topic. The particular change of contract specifications provides this study with a unique opportunity to investigate the impact of contract size on futures market characteristics. Our empirical findings suggest that although the change in the size of the futures contract have resulted in lower trading costs, it did not spur investors' interest in the Greek derivatives market. The results of this study have significant practical relevance in terms of futures market design decisions.